1995
DOI: 10.1139/b95-125
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of chloroplast DNA restriction site characters with morphological and isozyme data in Solanum sect. Lasiocarpa

Abstract: Chloroplast DNA restriction site characters were analyzed cladistically in species of Solanum sect. Lasiocalpa (subg. Leptostemonum), and results were compared with previously published analyses of morphological and isozyme characters. Cladistic analysis of the chloroplast DNA restriction site characters resulted in a single tree in which two main clades were detected: one comprised three morphologically distinct lowland Amazonian species, and the other included the Andean and the two Asian species. Character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 82 publications
(150 reference statements)
2
19
1
Order By: Relevance
“…The lack of well-supported resolution for each partition analyzed alone likely contributed to the lack of conflict observed in the results of the ILD test. The combined analysis is considered to be the most accurate representation of phylogenetic signal based on lack of apparent data conflict and the inherent benefits of the total evidence approach (Kluge 1989;Bruneau et al 1995;Nixon and Carpenter 1996;Graham et al 1998). Taxonomic Groupings and Support.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of well-supported resolution for each partition analyzed alone likely contributed to the lack of conflict observed in the results of the ILD test. The combined analysis is considered to be the most accurate representation of phylogenetic signal based on lack of apparent data conflict and the inherent benefits of the total evidence approach (Kluge 1989;Bruneau et al 1995;Nixon and Carpenter 1996;Graham et al 1998). Taxonomic Groupings and Support.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the two plastid trnK data sets arbitrarily divided at the start of the matK coding region are also found to be incongruent (P ϭ 0.01). This latter result indicates that there is significant incongruence in the data provided by one contiguous gene sequence (or "process partition"), suggesting within-data set homoplasy as another factor that can influence the results of incongruence analyses (see Bruneau et al, 1995;Siddall, 1997). It has been shown that different levels of homoplasy within data sets can render ambiguous the interpretation of P values generated by ILD or …”
Section: Resultsmentioning
confidence: 99%
“…Considering the vast amount of literature questioning the validity of partitioning data and supporting combined phylogenetic analyses (Kluge, 1989;Wheeler et al, 1993;Bruneau et al, 1995;Nixon and Carpenter, 1996;DeSalle and Brower, 1997;Siddall, 1997;Graham et al, 1998;Wenzel and Siddall, 1999), and the results obtained here with respect to the arbitrary partitioning of the data, we have decided to include all available data in a combined analysis designed to examine phylogenetic relationships for a group of organisms.…”
Section: Molecular Phylogeny Of Costaceaementioning
confidence: 99%
“…Cladistic analyses based on morphological characters exist for Solanum section Androceras (Nutt.) Marzell (Whalen 1979), section Lasiocarpa (Dunal) D'Arcy (Whalen et al 1981;Whalen and Caruso 1983;Bruneau et al 1995 (Whalen 1984), subgenus Potatoe (G. Don) D'Arcy (Spooner et al 1993), and subgenus Archaesolanum Marzell (Symon 1994). Recently, molecular phylogenetic studies have elucidated systematic problems in Solanum and the evolutionary placement of Solanum within the larger Solanoideae (Palmer and Zamir 1982;Hosaka et al 1984;Debener et al 1990;Spooner et al 1991;Olmstead and Palmer 1991, 1997Spooner and Sytsma 1992;Spooner et al 1993;Olmstead and Sweere 1994;Bruneau et al 1995;Bohs and Olmstead, in press;Olmstead et al, in press).…”
mentioning
confidence: 99%